TINGKAT NIAT PEMBELIAN ONLINE SHOP DI KALANGAN MAHASISWA UNIVERSITAS SYIAH KUALA - Gina Kembari Jasman, Permana Honneyta Lubis (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2017)
This study aims to examine perceive of easy to use, norm subjective, perceive of risk of purchase behavior intention via internet and perceive usefulness and attitudes toward purchasing via internet as a mediation variable. The sample used in this study is 200 respondents of Syiah Kuala University students who have accessed the internet. A Purposive Sampling technique is used as technique sampling. A Hierarchical Linear Modeling (HLM) is used as an analytical method to know the influence of the variables involved. The results of this study indicate that perceive easy to use has positive and significant effect on the perceive usefulness. Perceive ease of use, perceive usefulness have a positive and significant effect on attitude toward purchasing via internet. In addition, perceive easy to use, subjective norms, perceive usefulness, attitudes toward purchasing via the internet have a positive and significant effect on purchasing behavior intention via internet. While perceive of risk has insignificant effect on purchasing behavior intention via internet. Overall, these finding are consistent with the result of previous studies. Keywords: Perceive Ease of Use, Subjective Norms, Perceive of Risk, Perceive Usefulness, Attitudes Towards Purchasing Via Internet, Purchasing Behavior Intention Via Internet